Optimizing Marketing Strategies for Enhanced Sales Performance in the Travel and Tourism Sector - Kee, Daisy Mui Hung; Sirajudeen, Sameena; Hizer, Nur Hannah Amirah; Nasir, Nur Suraini; Rau, Svenja (AIBPM Publisher, 2024)
This study explores key influencing factors affecting marketing sales performance for the travel and tourism industry. Research has shown that the travel and tourism industries have become one of the important sectors. Due to uncertainties in today's highly competitive global economy, these industries have struggled to survive and sustain growth during the pandemic. Hence, it is justifiable to make further research on how to develop these industries. It is interesting to investigate factors that can enhance marketing sales performance for these industries. The literature review shows that sloganization, dynamic pricing and personal selling are three important key influencing factors. A conceptual model was proposed. Conclusion and limitations of this study are discussed in this study.